Vocation, formation, and theological education : interdisciplinary perspectives from Fuller Theological Seminary - Downs, David J., 1977-; Houston-Armstrong, Tina; Yong, Amos (Claremont Press, 2021)
This volume represents one set of reflections on issues of vocation, formation, and theological education in the first quarter of the twenty-first century. Each of the contributors to the volume is (or was, in one case) a faculty member at Fuller Theological Seminary, an institution that, like many others, has been wrestling seriously with the global transformation of theological education for at least the past decade. With the generous support of Fuller's Office of Vocation and Formation, the editors of this volume-all of whom at the time of the project's origins directed the PhD program in their respective schools (Downs in the School of Theology, Houston-Armstrong in the School of Psychology, and Yong in the School of Intercultural Studies)-invited colleagues to participate in an interdisciplinary conversation centered around questions of vocation and formation in our own institutional context. This book is the result of that stimulating project. With representative voices from each of these schools, we hope that the essays reflect the interdisciplinary conversations that shaped each contribution. -- from back cover.